Consumer Labels can Convey Polyphenolic Content: Implications for Public Health - Andrew L. Waterhouse (Clinical and Developmental Immunology)
Polyphenolics are a large group of related substances. Many of these, in fact much of that found in food, is composed of processing-derived substances too complex for complete identification. Recent studies have suggested likely benefits for diets high in polyphenols, particular in reducing heart disease mortality, but other benefits have also been suggested. A consumer label based on the major polyphenolic classes is both manageable and fairly informative as most foods do not contain all possible classes. Differences between class member can be significant, but data on individual substances is impractical and no data is certainly less informative. Equivalency scales may be useful but may skew content of many foods towards the high-equivalency substances, even while the full beneficial effects of each individual substance is poorly described.